Atualidade do pensamento social brasileiro - Elide Rugai Bastos (Sociedade e Estado, 2011)
Várias questões atualmente colocadas no âmbito das ciências humanas para o entendimento da sociedade foram, de vários modos, objeto da reflexão dos autores brasileiros ao longo dos anos: a problemática da emancipação, do direito à diferença, dos limites à liberdade, da definição da dignidade como projeto social, do reconhecimento, da exclusão/excludência, foram objetos recorrentes dos estudos sobre a formação nacional. Pretendo apontar, neste texto, como algumas reflexões dos anos 1950 e 1960 - brasileiras e latino-americanas - antecipam tais questões, mesmo sem terem desdobramento teórico sistemático. Several themes that animate contemporary human sciences in their painstaking efforts to come to terms with society have been, in different ways, at the very center of the agenda of Brazilian social scientists. The following are some of such issues: emancipation, the right to difference, the limits to freedom, the definition of dignity as a social project, recognition, exclusion, among others, have all been subjected to the scrutiny of sociologists concerned with the issue of Brazilian national formation. This article intends to indicate some of the reflections that colored the 1950s and 1960s scholarly scene in both Brazil and Latin America, which anticipated most of such themes, despite their unsystematic theoretical treatments.